Tourism, sustainability and environment: a sociological approach to the tourism management of the geographical space and the territory in Spain. - Sotelo Pérez, María (Observatorio Medioambiental, 2023)
The purpose of this study is to approach the sociological implications of territorial planning in Spain, addressing its implications in the field of Tourism, from an environmental perspective - from the field of sustainability-. In this way, it is based on the knowledge of the essential precepts of Territorial Planning, conceived as a technique, a public-social policy, focused around the processes of physical planning, the organization of economic activities - specifically, in our work, focused on tourism-, and in the territorial development, in its triple dimension, of the set of agents, elements and factors that define the tourism system, in our case in Spain, from the different scalar levels, the basis for the implementation of tourist activities.